Effects of three pesticides on the avoidance behavior of earthworms in laboratory tests performed under temperate and tropical conditions. - GARCIA, M. (2007)
Little research has been performed on the impact of pesticides on earthworms under tropical conditions. Taking into consideration the oftenlimited resources in tropical countries, simple screening tests are needed. Therefore, it was investigated whether three pesticides relevant for the Brazilian Amazon (benomyl, carbendazim, lambda-cyhalothrin) affect the avoidance behavior of the earthworm Eisenia fetida. The tests were performed for two days according to ISO guideline 17512 but were adapted to tropical conditions (i.e. test substrate, test organism and temperature). The results indicate that this test gives reproducible and reliable results. Toxicity values (NOEC, EC50) are lower than those determined in 14 day-acute mortality tests and are approximately in the same range such as those found in 56 day-chronic reproduction tests with the same earthworm species, which were performed in parallel. Therefore, the use of the earthworm avoidance tests is recommended as a screening tool for the risk assessment of pesticides.